2023
DOI: 10.1039/d3ra00789h
|View full text |Cite
|
Sign up to set email alerts
|

A review on arsenic in the environment: contamination, mobility, sources, and exposure

Abstract: Contamination, mobility, sources, and exposure of arsenic (one of the regulated elements) in the environment are investigated and discussed comprehensively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 222 publications
0
8
0
Order By: Relevance
“…The background concentration of As in soil mainly depends on the lithology and type of soils, ranging from 5 to 10 mg/kg [64]. Several authors showed that As concentration in soils of polluted areas varied from 126 to 1600 mg/kg [64]. In our study, the soil samples of five horticultural gardens had As contents higher than 100 mg/kg.…”
Section: Soil Vegetables and Risk Analysismentioning
confidence: 43%
See 1 more Smart Citation
“…The background concentration of As in soil mainly depends on the lithology and type of soils, ranging from 5 to 10 mg/kg [64]. Several authors showed that As concentration in soils of polluted areas varied from 126 to 1600 mg/kg [64]. In our study, the soil samples of five horticultural gardens had As contents higher than 100 mg/kg.…”
Section: Soil Vegetables and Risk Analysismentioning
confidence: 43%
“…The sub-acidic conditions of the investigated soils, in addition to the relatively high As concentration, affects arsenic mobility, increasing the phytoavailability and uptake by plants. The background concentration of As in soil mainly depends on the lithology and type of soils, ranging from 5 to 10 mg/kg [64]. Several authors showed that As concentration in soils of polluted areas varied from 126 to 1600 mg/kg [64].…”
Section: Soil Vegetables and Risk Analysismentioning
confidence: 99%
“…Arsenic proved a popular topic for element-specific reviews with no fewer than three being published during the period covered by this ASU. With reference to soils and waters, both Patel et al 99 (238 references) and Valskys et al 100 (177 references) discussed As contamination, quantification, sources, mobility and health hazards. Mihucz 101 (222 references) focused on As speciation and analysis in soil, water, foods and Ayurvedic medicines.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…Among these issues, heavy metal pollution has emerged as a serious problem due to its cumulative, toxic, and nondegradable nature, posing significant risks to both the natural environment and human health. , Arsenic, in particular, has been classified as the most toxic element by numerous organizations . Groundwater and soil contamination by arsenic has been reported in more than 105 countries worldwide, , especially in Asian countries. In nature, arsenic exists in the −3, 0, +3, and +5 oxidation states, but the toxicity of trivalent arsenic is 60-fold greater than that of pentavalent arsenic. As a result, arsenic is usually accumulated and stabilized as less toxic arsenate (e.g., Ca 5 (AsO 4 ) 3 OH, FeAsO 4 ) by the remediation technologies of arsenic in the atmosphere, water bodies, and other industrial outputs. , However, a significant amount of arsenic is produced in the form of highly toxic arsenic trioxide. According to data from the United States Geological Survey, global production of arsenic trioxide amounted to 61,000 tons in 2022, with only a small portion being used in pharmaceutical engineering, semiconductors, alloys, optical materials, and wood treatment.…”
Section: Introductionmentioning
confidence: 99%